Canadian Firm and Job Dynamics - Balakrishnan, Ravi (IMF Working Papers; Working Paper ;, 2008)
To understand better Canada's smooth reallocation of labor in response to the recent commodity price boom, but seemingly poor productivity performance, this paper examines job and firm dynamics in Canada relative to the United States. Overall, it finds that while Canada's labor market efficiency seems comparable to that of the United States, product market rigidities appear to be reducing Canada's capacity for creative destruction, hence undermining productivity growth.